Relationship between World Assumptions and Resilience in Psychological Counsellors: The Mediating Role of Self-Orientations - ERDEN ÇINAR, SEVAL; Erden, Seval (My University, 2020)
The purpose of the study was to examine the mediating role of self-orientations in the relationship between resilience and world assumptions of psychological counsellors. A total of 321 psychological counsellors, were recruited and 211 of them were women and 110 of them were men.  The ages of the participants ranged from 23 to 52. The Brief Resilience Scale, World Assumptions Scale, and Balanced Integration-Differentiation (BID) Scale were used as data collection tools. In the analysis of the data, descriptive statistics, Pearson Correlation Coefficient, as well as the Bootstrap method was used to analyze the mediation effects. The findings showed that the assumptions of benevolence, randomness, self-worth, and justice and self-orientation were positively related to psychological resilience. Results of the mediation analysis revealed that self-developmental and interrelational orientations had mediation effects on relationships between world assumptions and resilience as in the proposed model. Findings for the model tested in the study were discussed with the literature and the implications were given to field experts, researchers, and psychological counsellors.
Relationship between World Assumptions and Resilience in Psychological Counsellors